Narasi Kebangsaan dan Memori Kolektif: Studi Humaniora tentang Identitas Nasional dalam Masyarakat Majemuk - Ahmad Zainul Arifin Hasbullah; Siti Maryam Fathanah Lubis; Muhammad Lukmanul Hakim Santoso (PT. Panca Publishing Indonesia, 2026)
National narratives and collective memory play a crucial role in the formation and maintenance of Indonesian national identity amid ever-growing plurality. This study aims to analyze the construction of national narratives across various sites of collective memory and to identify patterns of national identity negotiation within Indonesia's plural society. A historical hermeneutics analysis method with a multi-source approach was employed, encompassing archival documents, monuments, museums, textbooks, and digital media from the period 2020 to 2024. The findings identify four constructive patterns: dominant singular narrative, competitive plural narrative, inclusive dialogical narrative, and contemporary hybrid narrative. The study concludes that collective memory is contestive and plural, wherein national identity is not given but continuously constructed through negotiation among various memory communities. Inclusive management of national narratives is a prerequisite for social cohesion in Indonesia's plural society